Penerapan Proyek Penguatan Profil Pelajar Pancasila Pada MTsN 3 Banyuwangi - Rofiah, Rofiah; Kibtiyah, Muhimatul (Inovasi: Jurnal Diklat Keagamaan, 2023)
Learning of Project of Strengthening The Pancasila Student Profile is a co-curricular learning that functions as a support for intra-curricular learning which is quite vigorously discussed in the Independent Curriculum. This project aims to improve the ability and build the character of students as Pancasila Students Profile through projects based learning related to problems that exist in the surrounding environment. This study aims to find out and analyze the application of the project learning to Strengthen Pancasila Student Profiles at Madrasah Tsanawiyah Negeri 3 Banyuwangi, the obstacles faced and how to overcome these obstacles. This type of research is qualitative research. The research was conducted in grade 7 for 7 months starting from August 2022 to February 2023. The participants in this study were 12 teachers at MTsN 3 Banyuwangi consisting of 10 class team coordinators and two project learning teachers, as well as several classes. Data collection in this study was carried out by means of semi structured interviews. The results of this study can be seen that MTsN 3 Banyuwangi has implemented the learning of The Pancasila Student Profile Strengthening Project but it is still not maximum yet due to several obstacles experienced especially in the project learning process. The solutions carried out by Madrasah are giving dissemination regarding this project or about independent curriculum more often, forming expert team invited to discuss problems in the field with the project team of each class, forming a class coordinator group (trough with the whats app group) consisting of 10 teachers from 10 classes to facilitate coordination, strengthening class teams with frequent coordination between team members and also coordinating with the expert team, the teacher makes plans in the form of project time plans, teaching modules or teaching materials, the team of experts supervises the class regarding the implementation of project learning. The implications of solutions that have been carried out by Madrasah are that the application of project learning is getting better and more optimal, this is reinforced by an increase in teachers understanding on project learning as evidenced by project products of each theme from students who are in accordance what the expert team wants. As well as the existence of a copy study from several other Madrasahs both from within the city and out side the city to MTsN 3 Banyuwangi and asking about the process of implementing the independent curriculum, especially project learning.